Frequency and molecular epidemiology of Aspergillus isolated from patients with suspicion of respiratory fungal infection - Oliveira, M. (2020)
Objective: The aim of this study was to determine the frequency of Aspergillus detected in respiratory samples from a cohort of patients with suspicion of fungal infection of the respiratory tract as well as to determine the susceptibility to azoles of the isolates from the Fumigati section. Methods: A retrospective study was performed involving samples obtained from 16 hospitals covering different districts of continental Portugal and Azores islands. One hundred and eighty-seven respiratory samples (101 bronchoalveolar lavage fluids, 52 bronchial lavages, 27 bronchial secretions, 6 expectorations and 1 bronchial aspirate) were collected between November 2011 and December 2017 from a cohort of 146 patients with suspicion of respiratory fungal infection (ages ranging from 20 to 87 years old). Demographic and clinical data were recorded. Detection of Aspergillus was done by culture, immunoenzimatic assay and/or molecular techniques. Aspergillus molecular identification to species level was performed by sequencing of the calmodulin and β-tubulin genes. To detect possible resistance to azoles, isolates belonging to section Fumigati were inoculated into Sabouraud dextrose agar media supplemented with 1 µg/ml or 4 µg/ml of voriconazole, 4 µg/ml of itraconazole and 0.5 µg/ml of posaconazole and their growth was observed and recorded after 7 days of incubation at 27ºC. Doubtful results were confirmed when possible by E-test and by real-time multiplex PCR for the detection of mutations in the Cyp51A gene. Results: Fifty-seven (39.0%) of the studied patients were positive for Aspergillus. From the cases with a positive culture (n=58) the species were identified by sequencing and belonged to six different sections. The most frequently isolated was the section Nigri (42.1%) followed by the Fumigati (33.3%) and Flavi sections (8.6%). Regarding the species, the most frequent was A. niger sensu stricto (33.9%) followed by A. fumigatus sensu stricto (32.1%). Nine cryptic species were also identified which frequency was 21.4%. In order to study the frequency of azole resistance in Fumigati isolates collected from the samples of this cohort as well from other biological products, 52 isolates - Aspergillus fumigatus sensu stricto (n=45), A. lentulus (n=4), A. udagawae (n=2) and A. pseudofelis (n=1) – were tested. The tested A. fumigatus sensu stricto isolates did not show resistance to azoles. An A. udagawae strain revealed low susceptibility to voriconazole (MIC was not determined due to loss of strain viability). An A. pseudofelis strain also showed decreased susceptibility to voriconazole (MIC =1 μg/ml) as well as to and itraconazole (MIC = 2 μg/ml). Conclusion: In this study, the genus Aspergillus was frequently isolated in the respiratory samples tested and a high number of cryptic species was detected. Although resistance to azoles was not a problem identified in the tested isolates, determination of the in vitro susceptibility profile and molecular identification of the Aspergillus species is essential to improve the diagnosis and management of aspergillosis since several cryptic species have intrinsic resistance to antifungal drugs.